Ўзбекистон гендер тенглиги ва гендер ривожланишнинг асосий кўрсаткичлари (SCIENCE and SOCIETY, 2022)
This article highlights the growing importance of supporting gender equality and women’s empowerment in Uzbekistan, in particular its commitment to women’s participation in decision-making, labor market competitiveness, and the joint fight against gender-based violence. and that women constitute the majority among those registered with the labor authorities, among those looking for work, and among those who are not employed after graduating from secondary schools, vocational schools and universities.